High-quality, single-layered epitaxial graphene fabricated on 6H-SiC (0001) by flash annealing in Pb atmosphere and mechanism. (20th February 2015) - Hu, T W; Liu, X T; Ma, F; Ma, D Y; Xu, K W; Chu, P K
Abstract: High-quality epitaxial graphene is produced on silicon carbide by flash annealing of 6H-SiC in a lead (Pb) atmosphere at ∼1400 °C for 30 s. Nearly three top bilayers of SiC are decomposed due to fast heating and cooling, and sublimation of Si atoms from SiC is retarded by the Pb atmosphere. The synergetic effects promote the growth of continuous single-layered graphene sheets on the SiC terraces, and a model is established to elucidate the effects and growth mechanism.